Effect of Breathing Exercise With Buteyko Methods Improveing Forced Expiratory Volume In One Second (Fev1) Score With Moderate Persistent Asthma - Mufarika, Mufarika; Mayangsari, Mulia; Haris, Mustofa; Andrian, Wahyu (Jurnal Keperawatan Muhammadiyah, 2019)
Objective: to know effect of breathing exercise with buteyko methods improveing forced expiratory volume in one second (FEV1) score with moderate persistet asthma.Methods: The research design used in this study is quasy-experiment. With the independent variable is breathing exercise with buteyko method and the dependent variable is forced expiratory volume in one second (fev1) score. This study used a simple random sampling technique which consisted of 9 treatment groups and 9 control groups with pair t test statistical test and man whitney test.Result: The results of the analysis using the man whitney test in the treatment and control groups obtained pvalue = 0.001 thes it can be concluded that there are differences between treatment and control groups.Conclusion: It is expected that this study provides benefits and knowledge as an alternative therapy in increasing FEV1 valuesin patients with moderate persistent asthma, and can be useful for patients with moderate persistent asthma to be able to practice breathing exercises with buteyko method independently, and it is expected that future researchers can do research on the effect of exercise breathing with buteyko method in individuals with moderate persistent asthma with longer interventions and other variables.